(untitled) (Journal of Bangladesh Academy of Sciences, 2014)
An investigation was made on the energy resolution of an active-target type gas counter operating in low-pressure He/CO2 mixed gas for studies of nuclear reactions such as (?, n) and (?, p) using radioactive nuclear beams (RNBs). The dependencies of effective gain and energy resolution on different parameters such as drift field, induction field and GEM voltages were studied. The energy resolution with adequate electric field configuretaion was found to be 3% in ?. DOI: http://dx.doi.org/10.3329/jbas.v37i2.17553 Journal of Bangladesh Academy of Sciences, Vol. 37, No. 2, 139-144, 2013